Transradial versus transfemoral intervention in ST-segment elevation myocardial infarction patients in Korean population - Li, Hu (Korean J Intern Med, 2018)
BACKGROUND/AIMS: Transradial intervention (TRI) is becoming the preferred method over transfemoral intervention (TFI) because TRI is associated with lower incidence of major bleeding and vascular complications. However, there has been limited published data regarding the clinical outcomes of TRI versus TFI in Korean patients with ST-elevation myocardial infarction (STEMI). METHODS: A total of 689 consecutive STEMI patients who underwent primary percutaneous coronary intervention (PCI) with drug-eluting stents (DESs) from January to December of 2009 at nine university hospitals were enrolled in this study. Mid-term angiographic and 12-month cumulative clinical outcomes of the TRI group (n = 220, 31.9%) were compared to those of the TFI group (n = 469, 28.1%). RESULTS: After propensity score matching, in-hospital complications and the 12-month major clinical outcomes during follow-up in the two groups were similar to each other. However, the incidence rates of repeat revascularization (6.4% vs. 0.5%, p = 0.003), target vessel revascularization (6.4% vs. 0.5%, p = 0.003), and major adverse cardiac events (MACE; 11.6% vs. 4.6%, p = 0.018) in the TFI group were higher than those in the TRI group during the 12-month of follow-up. CONCLUSIONS: In our study, TRI in STEMI patients undergoing primary PCI with DESs was associated with lower incidence of access site hematoma, 12-month repeat revascularization, and MACE compared to TFI. Therefore, TRI might play an important role in reducing bleeding complications while improving major clinical outcomes in STEMI patients undergoing primary PCI with DESs.